Health systems and HIV treatment in sub-Saharan Africa: matching intervention and programme evaluation strategies - Bärnighausen, Till; Bloom, David E.; Humair, Salal (Sexually transmitted infections, 2012)
Objectives National political commitment is likely to become particularly crucial to sustaining antiretroviral treatment programmes in the coming decade, as donor contributions to HIV funding decreases. The objective of this study is to synthesise information on existing indicators of political commitment to respond to national HIV epidemics. Methods The authors describe and critically evaluate the existing indicators and propose studies to validate them. Results Several indicators have been developed to measure governments' political commitment to respond to national HIV epidemics-the AIDS Program Effort Index, the United Nations General Assembly Special Session on HIV/AIDS Declaration of Commitment Indicators and the AIDS Policy Aggressiveness Indicators-but the validity of these measures has not been systematically assessed. The indicators differ in their intended use, collection methods, content categories, data coverage, and strengths and limitations. Several types of studies could be used to test indicator validity (based on indicator content, comparisons of the same indicator using different elicitation methods, relationship patterns between indicators, relations between indicators and other variables and the consequences of using the indicators). Conclusions The existing indicators of political commitment to respond to national HIV epidemics are useful for many purposes, including research, policymaking and advocacy. A range of studies could improve the understanding of indicator validity. New data collection and measurement approaches offer opportunities to improve how actors in the HIV community capture the complicated, multidimensional concept of political commitment